LIMCH1 protein expression associated with lymph node metastasis in breast cancer - V. V. Alifanov; L. A. Tashireva; M. V. Zavyalova; V. M. Perelmuter (Сибирский онкологический журнал)
Background. Lymph node metastasis in breast cancer is not only a variant of cancer progression, but is also associated with the development of hematogenous metastases. The LIMCH1 protein is involved in the mesenchymal type of migration due to the activation of non-muscle myosin IIA.The objective of the study was to investigate the association of different LIMCH1 protein expression variants with lymph node metastasis.Material and Methods. The retrospective study included 53 patients with invasive breast carcinoma of no special type. The study group included all molecular genetic types (luminal A, luminal B, HER2-positive and triple negative). The median age of the patients was 55.4 ± 14 years. According to the TNM classification, patients had stage T1–3N0–3M0 breast cancer. The patients did not receive preoperative chemotherapy. The expression of the LIMCH1 protein in tumor cells was assessed using immunohistochemistry. Anti-LIMCH1Prestige (HPA004184, Sigma Aldrich, Germany) and anti-LIMCH1-C-term (SAB2700402, Sigma Aldrich, Germany) antibodies were used.Results. Lymph node metastases were more frequent in patients with LIMCH1 protein expression in tumor cells. This is true for cytoplasmic expression of the LIMCH1 protein detected by the CH domain, but not for submembrane expression or expression of the LIMCH1 protein detected by the LIM domain, regardless of localization in the cell. This phenomenon was not associated with the morphological heterogeneity of breast cancer. The most unfavorable factor for worse metastasis-free survival is the combination of the presence of lymph node metastases and cytoplasmic expression of the LIMCH1 protein detected by the CH domain.Conclusion. The development of synchronous lymph node metastases in breast cancer is associated with the presence of cytoplasmic expression of the LIMCH1 protein detected by the CH domain in the primary tumor tissue.